POTENSI TUMBUH-TUMBUHAN DALAM MENCIPTAKAN RAGAM MATERIAL FINISHING UNTUK INTERIOR - Setiawan, Andereas Pandu (Institute of Research and Community Outreach - Petra Christian University, 2003)
Space always becomes the main study of interior design. It needs various considerations in the side of space shaper elements, space proponent elements, space fill-in elements, and space decorative elements. These element will appropriate with the goals of design if on the whole can appear the finishing. Shape which has the same aims in its concepts.Interior finishing as the final step of a design process determines the asthetic sense of the interior design, moreover it represents uniformity between design shape with interior design concepts. It is very important to creat an interesting finishing appearance of interior elements surfaces. Because of it inventions in field of finishing materials do needs to develop. Plants as natural materials have potentiality to create an enrich various interior finishing. Beside friendly to environments because of its nature which is easy to process by nature, they also can find in every part of Indonesia. Every plant from various interior of variety can be exploited and used as finishing materials. Such as for natural dye, mix materials for surface textures, and also being the main thing to create an interior surface appearance. Abstract in Bahasa Indonesia : Ruang selalu menjadi kajian utama dalam perancangan interior. Dalam perancangannya ruang memerlukan berbagai macam pertimbangan baik dari sisi elemen pembentuk ruang, elemen pendukung ruang, elemen pengisi ruang maupun elemen dekoratif ruang. Elemen-elemen yang tersusun tersebut akan sesuai dengan tujuan perancangan interiornya apabila secara keseluruhan dapat menampilkan wujud finishing yang sesuai dan tepat dengan maksud yang dikandung dalam konsep perancangannya. Mewujudkan penampilan finishing yang menarik dari sebuah permukaan bidang dalam elemen-elemen interior adalah sesuatu yang sangat penting, oleh karena itu adanya penemuan-penemuan baru di bidang material finishing sangat perlu dikembangkan. Tumbuh-tumbuhan sebagai material alami sangat berpotensi untuk menciptakan dan memperkaya perbendaharaan ragam jenis finishing interior. Selain ramah terhadap lingkungan karena sifatnya yang mudah terurai oleh alam, tumbuhan secara mudah dapat dijumpai dan didapati di Indonesia. Semua tumbuh-tumbuhan dari berbagai jenis dapat diolah dan dimanfaatkan sebagai material finishing untuk interior, baik perannya sebagai pewarna alami, sebagai material campuran pembentuk tekstur permukaan, maupun berperan tunggal sebagai material yang membentuk tampilan sebuah bidang permukaan dalam interior. Kata kunci : material, tumbuh-tumbuhan, finishing, interior.